2014
DOI: 10.1111/bjet.12145
|View full text |Cite
|
Sign up to set email alerts
|

Methodological capacity within the field of “educational technology” research: an initial investigation

Abstract: The academic study of educational technology is often characterised by critics as methodologically limited. In order to test this assumption, the present paper reports on data collected from a survey of 462 “research active” academic researchers working in the broad areas of educational technology and educational media. The paper explores their familiarity and expertise with various methods of data collection and analysis. Data from the survey highlight a preference for relatively basic forms of descriptive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 10 publications
1
39
0
6
Order By: Relevance
“…2 The three journals publish papers related to all education settings rather than focusing solely on a certain setting, such as higher education. 3 They are three of the four prominent educational technology journals (ie, CAE, BJET, LMT and the Australasian Journal of Educational Technology (AJET)) that are used by other researchers searching for education-technology-related empirical articles or authors (see Bulfin, Henderson, & Johnson, 2013;Bulfin et al , 2014). However, we dropped AJET from our study because it focuses solely on higher education settings.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 The three journals publish papers related to all education settings rather than focusing solely on a certain setting, such as higher education. 3 They are three of the four prominent educational technology journals (ie, CAE, BJET, LMT and the Australasian Journal of Educational Technology (AJET)) that are used by other researchers searching for education-technology-related empirical articles or authors (see Bulfin, Henderson, & Johnson, 2013;Bulfin et al , 2014). However, we dropped AJET from our study because it focuses solely on higher education settings.…”
Section: Methodsmentioning
confidence: 99%
“…However, we dropped AJET from our study because it focuses solely on higher education settings. 4 The three journals have broad geographical catchment, with authors from many parts of the world (Bulfin et al , 2014). To answer the first research question (How explicitly is existing theory identified in empirical educational technology research?)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Practicing social scholarship of integration, e‐researchers and collaborators use complex tools, emerging research methods (eg, social network analysis), and research teams to investigate interdisciplinary problems. Calls for methodological capacity building in the field of educational technology (Haßler, Major, & Hennessy, )—especially to prepare for work with large, digital data sets (Bulfin, Henderson, Johnson, & Selwyn, )—make practicing SSOI, with its exposure to different research traditions and cultures, even more timely. This dimension of scholarship posits that social problems require the collective efforts of a team—often using methods borrowed from computer science and increasingly influenced by biomedical and public health approaches grounded in epidemiology.…”
Section: Scholarship Reconsidered Today: Social Scholarshipmentioning
confidence: 99%
“…Journal articles that report quantitative results often do not include representative visuals or graphs (see Berlin & White, 2012;Braden, 1996;Bulfin, Henderson, Johnson, & Selwyn, 2014;de Villiers, 2007;McLaren, 2012;Yildiz, 2012). When graphs are included, these are often bar charts where the meaning of the data may not be immediately clear (Craig, Lang, & Fisher, 2008;Shea & Duncan, 2013).…”
Section: Alice Was Beginning To Get Very Tired Of Sitting By Her Sistmentioning
confidence: 99%